Workplace ostracism and employees' affective commitment: testing the role of resource depletion and psychological safety - Shahida Noor; Muhammad Abbas (Cogent Business & Management, 2024)
Prior research has examined the relationship between workplace ostracism with various work-related outcomes. However, relatively little is known about the mechanisms that link ostracism to work outcomes. This study uniquely contributes to the body of knowledge by examining the mechanisms through which workplace ostracism harms employees' affective commitment. The study examines the roles of resource depletion and psychological safety as underlying psychological mechanisms that link workplace ostracism to affective commitment. A three-wave time-lagged data collected from employees (N = 271) of the service industry in Pakistan indicates that workplace ostracism may reduce employees' psychological safety and contribute to resource depletion. Moreover, workplace ostracism reduces affective commitment by depleting employees' psychological resources and psychological safety.
Keywords: 650; Workplace ostracism; resource depletion; psychological safety; affective commitment; Quantitative